Catalytic Performance Of Multi-Component Copper-Based Catalyst For Direct Carbon Dioxide Hydrogenation To Methanol - Koh, Mei Kee (2018)
Methanol production from direct CO2 hydrogenation is a useful strategy to utilize CO2 and a practical approach to sustainable development. Improving the efficiency of the reaction is crucial for encouraging the decentralize of the technology and this is achievable via the development of active catalysts. After rigorous screenings, multi-component 0.6Cu/0.15ZnO/0.05MnO/1.0SBA-15 (CZM/SBA-15) was developed in this study. The introduction of SBA-15 as catalyst support effectively improved the catalyst texture. The addition of MnO as promoter created strong interactions between CuO and other oxide species in the catalyst. Besides, MnO also promoted the formation of small copper crystallites. In this way, the hydrogen adsorption capacity of the catalyst was enhanced, leading to strong hydrogenation strength. A moderate interaction between CZM/SBA-15 and CO2 molecules was found crucial for enhancing CO2 conversion. The methanol selectivity was remarkably increased to more than 90% due to the availability of metal-oxide(s) interfacial area to stabilize reaction intermediates. Then, the morphological impact of porous supports on copper crystallites and effective diffusivity (catalyst pore-geometry dependent coefficient) of catalyst were investigated. The porous supports selected for investigation were SBA-15, MCF and KIT-6. Among all, KIT-6 supported catalyst (CZM/KIT-6) presented the most superior properties. The morphology of KIT-6 deterred mesopore plugging and favoured the formation of small copper crystallites. CZM/KIT-6 also possessed greater resistance to copper crystallite growth and loss of copper surface area during reaction due to the pore-confining effect of the porous support and the larger inter-crystallite spacing between copper crystallites. The high effective diffusivity of CZM/KIT-6 enhanced the transfer of reactant molecules to active sites and the removal of reaction products. Next, the effect of weight-hourly space velocity (WHSV, 8-120 L/gcat.h), reaction temperature (160-260°C) and pressure (1.0-5.0 MPa) on the performance of CZM/KIT-6 were investigated. The response of CO2 conversion and methanol selectivity to these parameters strictly obey the reaction thermodynamic. In stability study, the performance of CZM/KIT-6 during 120 h time-on-stream was maintained at high level. Compared to the pre-reduced catalyst, the copper crystallite growth of CZM/KIT-6 spent in the stability experiment was 50.7% and the loss of copper surface area was 33.9%. On the average, the CO2 conversion attained was 27.6% and the methanol selectivity was 88.3%. The average methanol yield was 24.4% and this corresponds to methanol formation rate of 71.6 mol/kgcat.h.